2009
DOI: 10.1016/j.iref.2008.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The choice of market entry mode: Greenfield investment, M&A and joint venture

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 10 publications
0
48
0
Order By: Relevance
“…Raff, Ryan, and Stahler (2009) have further shown that cross-border acquisitions might not always present an optimal solution to an acquiring firm that is looking for a new market. The other two viable options are greenfield investment and joint venture.…”
mentioning
confidence: 99%
“…Raff, Ryan, and Stahler (2009) have further shown that cross-border acquisitions might not always present an optimal solution to an acquiring firm that is looking for a new market. The other two viable options are greenfield investment and joint venture.…”
mentioning
confidence: 99%
“…It can be argued that if the foreign partner cannot see immediate gains in a highly volatile market, it is likely that it will pull out quickly. Indeed, many large corporations see IJVs as a transitional mode on their way to the establishment of wholly owned subsidiaries (Prahalad and Lieberthal 2003;Raff et al 2009;Wassmer 2010). Such practice triggers doubt about sustainable cooperation, which certainly casts a shadow on current performance of South African -US joint ventures.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…5 Our results are likely to have important implications for a firm's inter-temporal choice of entry mode. See, for instance, Haller (2009), Lahiri (2009, Kurata et al (2009) and Raff et al (2009).…”
Section: Endnotesmentioning
confidence: 99%